Analisis Kebijakan Mengatasi Kemacetan di DKI Jakarta dengan Metode Analisis Hirarki Proses - khayu rohmi (Journal of Law and Administrative Science, 2023)
This study aims to determine the formulation of the congestion problem in DKI Jakarta by using the Process Hierarchy Analysis method and presenting policy alternatives to the congestion problem. This research uses a qualitative method which is a literature study. The results of the study show that the vehicle aspect is the root cause of congestion because owning a private vehicle has low economic value. Based on the policy analysis that has been carried out, the estimated number of vehicles in DKI Jakarta in 2025 will reach 29,150,000 units. Policies on controlling private vehicle ownership and improving an integrated public transportation system are policies that meet the policy criteria for overcoming congestion problems in DKI Jakarta in this study.